Biofabrication of Multiplexed Electrochemical Immunosensors for Simultaneous Detection of Clinical Biomarkers in Complex Fluids. Issue 24 (19th June 2022) - Timilsina, Sanjay S.; Ramasamy, Mohanraj; Durr, Nolan; Ahmad, Rushdy; Jolly, Pawan; Ingber, Donald E.
Abstract: Simultaneous detection of multiple disease biomarkers in unprocessed whole blood is considered the gold standard for accurate clinical diagnosis. Here, this study reports the development of a 4‐plex electrochemical (EC) immunosensor with on‐chip negative control capable of detecting a range of biomarkers in small volumes (15 µL) of complex biological fluids, including serum, plasma, and whole blood. A framework for fabricating and optimizing multiplexed sandwich immunoassays is presented that is enabled by use of EC sensor chips coated with an ultra‐selective, antifouling, and nanocomposite coating. Cyclic voltammetry evaluation of sensor performance is carried out by monitoring the local precipitation of an electroactive product generated by horseradish peroxidase linked to a secondary antibody. EC immunosensors demonstrate high sensitivity and specificity without background signal with a limit of detection in single‐digit picogram per milliliter in multiple complex biological fluids. These multiplexed immunosensors enable the simultaneous detection of four different biomarkers in plasma and whole blood with excellent sensitivity and selectivity. This rapid and cost‐effective biosensor platform can be further adapted for use with different high affinity probes for any biomarker, and thereby create for a new class of highly sensitive and specific multiplexed diagnostics. Abstract : Multiplex rapid and cost‐effective electrochemical immunosensor platform is coated with antifouling nanocomposite for simultaneous detection of multiple disease biomarkers in complex biological fluids including unprocessed whole blood and plasma with excellent sensitivity and selectivity without background signal.